Neither male age nor semen parameters influence clinical pregnancy or live birth outcomes from IVF - Mariappen, U.; Keane, Kevin; Hinchliffe, P.; Dhaliwal, S.; Yovich, John (2018)
Advanced age is an increasing trend for both males and females seeking in vitro fertilization (IVF). This retrospective cohort study investigated the outcomes of 1280 IVF-related treatment cycles, selecting the first treatment for couples utilizing autologous gametes and who underwent single fresh embryo transfer. Males aged 40–49 years had a 52% reduction in normal sperm motility, while it was markedly reduced by 79% at 50 years or older. However, neither semen parameters nor male age were predictive of clinical pregnancy or live birth chance. In a combination of age groups, cases with Younger Females had the greatest chance of successful outcomes and this was independent of having a younger or older male partner. Specifically, Young Female-Young Male combinations (= 35 years) were the most likely to succeed in achieving a clinical pregnancy or live birth (OR 2.84, p < 0.0005 and 3.34, p < 0.0005, respectively), while the Young Female-Old Male group (= 35 and >35 years, respectively) had a similar increased chance (OR 2.07, p < 0.0005 and 2.78, p < 0.0005, respectively). This trend strengthened as the Female age cut-off was increased to 38 years and the Male age cut-off increased to 40 or 42 years. Consistently, the groups comprising a Young Female with either a Young Male or Old Male outperformed the groups with an Old Female. Our finding confirms reduced fecundity with advancing female age as the most important parameter. The outcomes were not significantly influenced by semen parameters or male age with respect to the likelihood of clinical pregnancy or live birth.